Digitalisasi Kebijakan Kepemimpinan Hijau dalam Pengelolaan Sampah: Strategi Pemerintah Daerah dalam Menerapkan Smart Waste Management di Kabupaten Enrekang - Nuha, Uli; Danindra, Fuad; Sunarti, Sunarti; Selistiawati, Selistiawati; Akbar, Imam; As’adiyah, Rahmi Budi (Universitas Muhammadiyah Sorong, 2025)
This study aims to examine the implementation of green leadership policies to support the digitalization of waste management through the Smart Waste Management (SWM) system in Enrekang Regency. The method used was Research and Development (R&D) with the ADDIE model, encompassing needs analysis, design, development, implementation, and evaluation. The main innovation of this study was the development of a web-based application for real-time waste reporting and monitoring. The results showed positive support from stakeholders, particularly the Environmental Agency and community users. However, implementation still faces obstacles such as inadequate regulations, limited human resource capacity, and suboptimal digital infrastructure. Through a SWOT analysis, strategies were formulated to strengthen policies and increase capacity to address these challenges. The implementation of digital technology has been shown to improve operational efficiency, accountability, and community participation. The application's easily accessible features help overcome communication barriers and increase environmental awareness. However, network limitations and the need for training for sanitation workers are obstacles that need to be addressed. This study emphasizes the importance of concrete policy support and sustainable funding for the digital transformation of waste management to be effective and serve as a model for other regions.